PEMANFAATAN LIMBAH TANAMAN TEBU UNTUK PAKAN SAPI - Akhadiarto, S. (Jurnal Rekayasa Lingkungan)
Up to the present time the compost heap of sugar cane has not yet been untilized to the greatest extent. The compost heap, however, has been a major animal feed. In Indonesia about 6.49 million sugar cane tops, 2.78 million ton kletekan and 1.86 million ton sugar sogolan can be obtained each year. By product of sugar processing can yield bagasse, blotong and molasses. All of these by products are potential as a substitute for common forage in ruminants particularly during a relatively long dry season as long protein sources provided. On the other hand the supply of animal feed is becoming scarce and expensive. The farm land growth is limited, especially in dry season. With regard to the potentials mentioned along with animal feed technology, the compost heap of the sugar cane can be converted into essential animal feed. The waste of sugar cane can be processed become wafer and the use can reached 50 ? 55 % from the total of the forage in ruminants.Key words : waste, sugar can, forage, wafer, ruminants.